Coopetition and innovation: A review and research agenda. (April 2023) - Corbo, Leonardo; Kraus, Sascha; Vlačić, Božidar; Dabić, Marina; Caputo, Andrea; Pellegrini, Massimiliano M.
Abstract: The proliferation of research on innovation-related coopetition calls for a more unified understanding of the current state of knowledge in this domain. Previous reviews on coopetition, however, fall short when it comes to putting innovation at the core of their analysis, often relegating the topic to one of the research themes/dimensions of coopetition, or considering innovation to be a promising area for future research. We fill this gap by systematically reviewing two decades of research on coopetition and innovation. We apply Multiple Correspondence Analysis (MCA) methods to a sample of 128 articles from academic journals published in the field of coopetition and innovation, revealing the major research themes, the theories and methods used, the levels of analysis, and the contexts explored. The holistic representation of coopetition and innovation research hinges upon multiple theories, including the resource-based view, the knowledge-based view, the network view, and the behavioral view, while predominantly focusing on strategy; innovativeness; value creation, appropriation and performance; appropriability and protection; and organizational culture. Given the increasing scholarly interest in both coopetition and innovation, this study proposes fruitful research avenues, and discusses their implications for both theory and practice. Highlights: Innovation-related coopetition has long been recognized as a source of competitive advantage. This review provides a synthesis of the fragmented literature at the intersection between coopetition and innovation. This review reveals the key contributions to the field and outlining emerging themes and promising future research avenues.